Determination of Factors Affecting Mortality of Patients with Sepsis in a Tertiary Intensive Care Unit - BALCAN, MEHMET BARAN; KARAKURT, SAİT; OLGUN YILDIZELİ, ŞEHNAZ (BILIMSEL TIP PUBLISHING HOUSE, 2015)
OBJECTIVES: Sepsis is a disease with high mortality that is frequently observed in intensive care units. This study aimed to determine the risk factors affecting mortality of patients with sepsis who were followed up in the intensive care unit (ICU). We aimed to contribute to literature by evaluating the relationship between mortality and pro-brain natriuretic peptide (pro-BNP9), C-reactive protein (CRP), thrombocyte count, Acute Physiology and Chronic Health Evaluation (APACHE) II score, Sequential Organ Failure Assessment (SOFA) score, duration of hospitalization in the intensive care unit, and the presence of multidrug-resistant microorganism. MATERIAL AND METHODS: Patients hospitalized in ICU because of the diagnosis of sepsis and septic shock between December 2010 and June 2012 were included in this retrospective study. RESULTS: A total of 141 patients, including 74 male (52.5%) and 67 female (47.5%) patients, were involved in the study, and the median age was 66.8 +/- 17.9 years. Sixty-nine patients (48.9%) were discharged from the ICU; however, 72 patients (51.1%) were exitus. Multi-drug-resistant microorganism was detected in 34 patients (24.1%). The patients' median SOFA score was 9.16 +/- 3.16, median APACHE-II score was 24.9 +/- 7.83, and median duration of hospitalization in the ICU was 8.44 +/- 11.61 days. It was found that mortality rate significantly increased in patients with the APACHE-II score of 24.5 and over, SOFA score of 8.5 and over, pro BNP value of 7241 ng/L and over, and CRP value of 96.5 mg/dL and over. Mortality rate was detected to be higher in patients undergoing invasive mechanical ventilation than in patients undergoing non-invasive mechanical ventilation. When thrombocyte count and mortality were associated with each other, it was found that the median value was 86000 mg/dL in exitus patients, whereas it was 185000 mg/dL in patients discharged from the ICU. CONCLUSION: It was revealed that increased APACHE-II score, increased SOFA score, increased pro BNP score, increased CRP, the presence of multidrug-resistant microorganism, and decreased thrombocyte count elevated the rate of mortality. However, no relationship was observed between the duration of hospitalization in the ICU and mortality.
Keywords: Sepsis; mortality; intensive care; VENTILATOR-ASSOCIATED PNEUMONIA; SOFA SCORE; MECHANICAL VENTILATION; NATRIURETIC PEPTIDE; SEPTIC SHOCK; PROCALCITONIN; DIAGNOSIS; MARKERS; PROTEIN